Cultivating Creativity and Innovation in the School Curriculum for the 21st Century: Opportunities and Challenges - Isabirye, AK; Moloi, KC; Lebelo, RS; Khan, S (Journal of Ecohumanism, 2025)
The present educational environment is confronted with the urgent need to undergo transformation and adjustment to meet the swiftly evolving requirements of the 21st century. This study examines the crucial necessity of fostering creativity and innovation in educational curricula to enhance the relevance of learners for the future. The analysis identified four primary themes using a literature review approach. This study examines the significance of creativity and innovation in educational curricula, the necessity to transition from conventional teaching methods to learner-centered approaches, the impact of technology on transforming educational practices, and the importance of teacher training and professional development. The findings emphasise the need for a fundamental educational shift prioritising the human learner and utilizing creativity, innovation, and technology to cultivate the abilities and competencies needed for future professional achievements. Hence, the study offers suggestions for educational policy, curriculum design, and teacher development. Furthermore, future study areas are suggested to explore empirical data and optimal methods for integrating creativity and innovation into education in the 21st century.